Seychelles : Public Sector Debt and Prospects for Successful Economic Reform - Kojo, Naoko C. (World Bank, Washington, DC, 2012)
Seychelles is at a development crossroads. With public sector debt at over 200 percent of Gross Domestic Product (GDP), manifested by years of poor macroeconomic management and rigid economic structure, the economy has been experiencing a serious downturn since the beginning of the 2000s. While real GDP contracted by cumulative nine percent for the past four years, the significantly overvalued rupee has led to a loss of export competitiveness, leading to persistent balance of payments difficulties. Following independence in 1976, Seychelles adopted a state-led development model, in which the Government plays a dominant role in every segment of the economy through extensive controls and regulations. It intervened directly in manufacturing, distribution, trade and other economic activities through its parastatals, often at the expense of private sector development. Provision of education and health services was predominantly the responsibility of the Government. Seychelles is faced with formidable challenges in the years ahead. With public sector debt at some 200 percent of GDP, manifested by decades of poor policy management, there is no painless solution to Seychelles debt predicament. For Seychelles the primary tool to reduce the debt burden, and turn the economy back to a sustained growth path is the implementation of a comprehensive macroeconomic reform program, with a strong emphasis on fiscal adjustments, privatization, exchange rate realignments and structural reforms. Without a significant change in policy direction, Seychelles medium-term prospects are bleak. Continuation of the present policies will neither mitigate the acute foreign exchange shortages nor further build-up of debt, which will be even more damaging in the future. This paper is structured as follows. Section 2 presents the basic facts about Seychelles public sector debt and analyzes its burden and sustainability. Section 3 then discusses the medium-term economic outlook, assuming that no significant economic adjustments are made. Section 4 then seeks ways to reduce Seychelles public sector debt to a more sustainable level, and discusses a comprehensive macroeconomic reform package that is needed to achieve this goal. Section 5 concludes the paper.